A Checklist for Implementing Rural Pathways to Train, Develop and Support Health Workers in Low and Middle-Income Countries - O'Sullivan, Belinda; Chater, Bruce; Bingham, Amie; Wynn-Jones, John; Couper, Ian; Hegazy, Nagwa Nashat; Kumar, Raman; Lawson, Henry; Martinez-Bianchi, Viviana; Randenikumara, Sankha; Rourke, James; Strasser, Sarah; et al. (Frontiers in Medicine, 2020)
Background: There is an urgent need to scale up global action on rural workforce development. This World Health Organization-sponsored research aimed to develop a Rural Pathways Checklist. Its purpose was to guide the practical implementation of rural workforce training, development, and support strategies in low and middle-income countries (LMICs). It was intended for any LMICs, stakeholder, health worker, context, or health problem. Method: Multi-methods involved: (1) focus group concept testing; (2) a policy analysis; (3) a scoping review of LMIC literature; (4) consultation with a global Expert Reference Group and; (5) field-testing over an 18-month period. Results: The Checklist included eight actions for implementing rural pathways in LMICs: establishing community needs; policies and partners; exploring existing workers and scope; selecting health workers; education and training; working conditions for recruitment and retention; accreditation and recognition of workers; professional support/up-skilling and; monitoring and evaluation. For each action, a summary of LMICs-specific evidence and prompts was developed to stimulate reflection and learning. To support implementation, rural pathways exemplars from different WHO regions were also compiled. Field-testing showed the Checklist is fit for purpose to guide holistic planning and benchmarking of rural pathways, irrespective of LMICs, stakeholder, or health worker type. Conclusion: The Rural Pathways Checklist provides an agreed global conceptual framework for the practical implementation of “grow your own” strategies in LMICs. It can be applied to scale-up activity for rural workforce training and development in LMICs, where health workers are most limited and health needs are greatest.